THE MORALISATION OF THE SUBJECT THROUGH HONESTY IN BRAZILIAN TEXTBOOKS FOR YOUTH AND ADULT EDUCATION - Anderson de Carvalho Pereira (Universidad Nacional del Nordeste, 2022)
Some didactic books used in the field of Youth and Adult Education (YAE) in Brazil, when dealing with everyday issues, identify the common theme with a moral code. In the analysis presented here, the theme of honesty is highlighted. Based on an evidential and discursive research, which included a historical review on the topic of honesty in Brazil, we selected from the materiality composed by these textbooks seven discursive sequences derived from this zone of meanings about honesty. Our aim was to analyse who this subject is, what place the book constructs and what sayings and imaginary formations in this semantic and discursive universe conceal the ideological evidence of a moral code. We conclude that this option, as we also indicated in the discursive sequences analysed here, indicates that the YAE didactic books analysed assume that the YAE subject-student is immersed in a lack of knowledge to be circumvented and resolved by means of a prior selection, a label for which the textbook guarantees a refuge in order to approach a moralisation. By accusing a YAE subject of morality and honesty, these textbooks subject him or her to the individual form of the 'good subject' of YAE.